Yeasts found on an ephemeral reproductive caste of the leaf-cutting ant Atta sexdens rubropilosa - Arcuri, Silvio Lovato [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Paixo Melo, Weilan Gomes da [UNESP]; Nagamoto, Nilson Satoru [UNESP]; Komura, Dirce Leimi; Rodrigues, Andre [UNESP] (Springer, 2014)
Winged males of leaf-cutting ants are considered an ephemeral reproductive caste only produced before the mating flight season. Although much is known about the yeast diversity found in fungus gardens of attine ants, no study has focused on the yeasts associated with males of leaf-cutting ants. Here, we surveyed the yeasts on the integuments of males of Atta sexdens rubropilosa and assessed their potential role in the attine ant-microbe symbiosis. Using culture-dependent techniques, we found yeasts to be abundant on the integuments of males (54.5 %, n = 200 alates). A total of 242 yeast strains were obtained representing six orders, ten genera and 25 species. Strains of Aureobasidium, Cryptococcus, Hannaella and Rhodotorula were prevalent on the integuments and likely originated from the fungus garden of the parental nest or from the soil. The majority of strains (87.1 %) produced at least one of the evaluated enzymes: pectinase, polygalacturonase, cellulase, xylanase, ligninases and lipase. Aureobasidium pullulans accounted for the highest number of strains that produced all enzymes. In addition, yeasts showed the ability to assimilate the resulting oligosaccharides, supporting observations of other studies that yeasts may be involved in the plant biomass metabolism in the fungus gardens. Because winged males harbor several yeasts with putative functional roles, these fungi may take part and be beneficial in the microbial consortia of the new incipient nest.
Keywords: Insect; Fungi; Dispersal; Plant-degrading enzymes; Nuptial flight